It's not just a brand name: The impact of language on consumer attitude and behavior - Ernest Cyril, de Run; Yee, Teh Chin; Khalique, Muhammad (International Journal of Research Studies in Management, 2012)
This paper notes the impact of language choice in a brand name on consumer’s response. This was measured based on three different language based brand names in the same product category (coffee). The brand names were Aik Cheong, Kopimas, and Power Root, representing Chinese, Malay, and English language respectively. Speech Accommodation Theory (SAT) is used as the basis for this paper as it indicates that a group prefers its own language and will respond positively. Data was collected from Chinese respondents throughout Malaysia using a survey. Questions were from past measurement scales utilizing a 6 point forced scale. The findings indicate that respondents preferred English and Chinese language brand name over Malay language brand name and there was no difference in response for English and Chinese language brand name. Malay language was the least preferred. This paper is limited by the method, breath and scope of data collection.